2006
DOI: 10.1007/s00726-006-0474-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-alanine supplementation on the onset of neuromuscular fatigue and ventilatory threshold in women

Abstract: This study examined the effects of 28 days of beta-alanine supplementation on the physical working capacity at fatigue threshold (PWCFT), ventilatory threshold (VT), maximal oxygen consumption (VO2-MAX), and time-to-exhaustion (TTE) in women. Twenty-two women (age+/-SD 27.4+/-6.1 yrs) participated and were randomly assigned to either the beta-alanine (CarnoSyn) or Placebo (PL) group. Before (pre) and after (post) the supplementation period, participants performed a continuous, incremental cycle ergometry test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
3
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 25 publications
6
132
3
2
Order By: Relevance
“…We hypothesised that β-alanine supplementation would improve time trial performance given the previously reported in uence of β-alanine on the ventilatory threshold 20 and the potential for an increase in muscle carnosine to increase the calcium sensitivity of slow and fast twitch muscle bres and enhance calcium release in slow twitch bres 3 . However, the strength of the currently available evidence to support the e ects of carnosine on calcium handling is limited 2,9 , with only one study 3 being conducted on human muscle bres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesised that β-alanine supplementation would improve time trial performance given the previously reported in uence of β-alanine on the ventilatory threshold 20 and the potential for an increase in muscle carnosine to increase the calcium sensitivity of slow and fast twitch muscle bres and enhance calcium release in slow twitch bres 3 . However, the strength of the currently available evidence to support the e ects of carnosine on calcium handling is limited 2,9 , with only one study 3 being conducted on human muscle bres.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a graded exercise test lasting ~19 minutes using untrained female participants, S et al 20 reported no e ects of β-alanine on maximal oxygen consumption but did report an increase in the time to exhaustion, as well as a delay in the onset of neuromuscular fatigue and an increase in the ventilatory threshold at submaximal workloads. ese ndings indicate the potential for β-alanine supplementation to increase performance during endurance based exercise.…”
Section: Introductionmentioning
confidence: 99%
“…day -1 ), although the VO 2 -max did not change. Also the physical working capacity at the fatigue threshold, determined by EMG of the vastus lateralis during cycling, increased significantly by beta-alanine supplementation in young [89] and aged [90] population. These studies were all performed in untrained subjects.…”
Section: Exercise Types That Benefit From Beta-alanine Supplementationmentioning
confidence: 95%
“…The total work done (TWD) during a cycle capacity test at 110% of their maximal power (duration of ~2.5 min) increased following 4 and 10 weeks of beta-alanine supplementation (+13% and +16.2% respectively). During an incremental cycling exercise test (starting at 40W and increasing with 20W every 3 min until exhaustion) in untrained women, Stout et al [89] found that the ventilatory threshold (+13.9%) and the time to exhaustion (+2.5%) significantly increased after 28 days of beta-alanine supplementation (6.4 g . day -1 ), although the VO 2 -max did not change.…”
Section: Exercise Types That Benefit From Beta-alanine Supplementationmentioning
confidence: 99%
“…Females also require lower levels of BA supplementation to obtain similar relative increases in carnosine compared to males (9). In women, BA increases time to exhaustion (10), and decreases feelings of perceived exertion (11). These data, taken together with the fact carnosine loading is further augmented in trained muscles (12), indicates trained females may be more sensitive to BA supplementation with regard to increasing carnosine concentrations.…”
mentioning
confidence: 99%